2021
DOI: 10.1021/jacs.1c04142
|View full text |Cite
|
Sign up to set email alerts
|

Low Density Interior in Supercooled Aqueous Nanodroplets Expels Ions to the Subsurface

Abstract: The interaction between water and ions within droplets plays a key role in the chemical reactivity of atmospheric and man-made aerosols. Here we report direct computational evidence that in supercooled aqueous nanodroplets a lower density core of tetrahedrally coordinated water expels the cosmotropic ions to the denser and more disordered subsurface. In contrast, at room temperature, depending on the nature of the ion, the radial distribution in the droplet core is nearly uniform or elevated toward the center.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 90 publications
2
29
0
Order By: Relevance
“…We think that the increased exclusion of the ions to the subsurface as temperature decreases is due to an improved H-bonded coordinated network in the droplet interior. The differences in the H-bonded network in the interior and subsurface in supercooled droplets have been presented in our previous research . At supercooling, both the CIP and SSIP are mainly formed in the outer portion of the subsurface, where the dielectric constant is expected to be higher than that at 300 K. The higher dielectric constant at lower temperature may lead to a decrease in the free energy difference between the CIP and SSIP, which is consistent with the free energy profile at 200 K shown in Figure a.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…We think that the increased exclusion of the ions to the subsurface as temperature decreases is due to an improved H-bonded coordinated network in the droplet interior. The differences in the H-bonded network in the interior and subsurface in supercooled droplets have been presented in our previous research . At supercooling, both the CIP and SSIP are mainly formed in the outer portion of the subsurface, where the dielectric constant is expected to be higher than that at 300 K. The higher dielectric constant at lower temperature may lead to a decrease in the free energy difference between the CIP and SSIP, which is consistent with the free energy profile at 200 K shown in Figure a.…”
Section: Resultssupporting
confidence: 87%
“…The free-ion configurations account for ≈70% of the total number. In previous research we have found that the supercooled droplets with N > 200 exhibit heterogeneity that is manifested by three regions: a bulk-like interior, a subsurface, and a surface (Figure ). In N = 776 the distances from the droplet’s COM that delimit these regions are R B = 7.4 Å, R V = 14.8 Å, and R e = 17.7 Å (where R e denotes the equimolar radius), respectively.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations